2019
DOI: 10.1111/jan.14137
|View full text |Cite
|
Sign up to set email alerts
|

The level of sense of coherence among Swedish nursing staff

Abstract: Aim To explore the level of sense of coherence among Swedish nursing staff. Design: An explorative quantitative study design was adopted using a short form for measuring sense of coherence. Methods Data were collected in January 2018 from nurses working in full‐time positions at two hospitals in Western Sweden. A total of 93 nurses completed the 13 item questionnaire measuring sense of coherence. Descriptive statistics were applied to obtain means and standard deviations. Spearman's rank correlation was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
6
32
1
Order By: Relevance
“…On the other hand, the participants in this study showed a high SOC, similar to the scores found in previous studies [43]. High levels of SOC among healthcare professionals have been associated with better health status, more work engagement, and fewer work-related family conflicts [44].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the participants in this study showed a high SOC, similar to the scores found in previous studies [43]. High levels of SOC among healthcare professionals have been associated with better health status, more work engagement, and fewer work-related family conflicts [44].…”
Section: Discussionsupporting
confidence: 88%
“…Despite our findings, reports on sex differences vary and it remains an unstable predictor for burnout or resilience [25,41,42]. Older age, on the other hand, has been reported as a strong predictor for greater resilience such as SOC and lower burnout levels [24,38,40,62]. Although previous studies were not all in agreement, older caregivers may have developed stronger beliefs in their own ability to deal with stressful situations with growing experience and years of employment, using their available resources more effectively [27].…”
Section: Discussioncontrasting
confidence: 68%
“…As far as we know, research on social support and sense of coherence among registered nurses is much limited. Previous studies had shown that a sense of coherence was an important factor to deal with stress and burnout during the nursing process and was related to job satisfaction (Eriksson, Kerekes, Brink, Pennbrant, & Nunstedt, ). Perceived professional benefits is an indication of the cognition of chronic work‐related feelings which contains job satisfaction and personal growth.…”
Section: Introductionmentioning
confidence: 99%